The orthodontist's profile in Minas Gerais - Luiz Fernando Eto; Valéria Matos Nunes de Andrade (Dental Press Editora, 2012)
OBJECTIVE: Due of the growing number of orthodontists and courses in Orthodontics, interest has grown in having a profile of these practitioners in Minas Gerais state (Brazil), showing how do they work in order to promote excellence in orthodontics, showing the most used techniques, the changes in the target public, and other views that impact on the future of the specialty and professional groups. METHODS: Questionnaires were sent to all orthodontists registered with the Regional Council of Dentistry of Minas Gerais (Conselho Regional de Odontologia de Minas Gerais, CRO-MG) until March 30, 2005, consisting of 722 professionals. Questionnaires were sent back by 241 (33%) professionals. CONCLUSIONS: This study clarified some relevant aspects about the profile of orthodontists in Minas Gerais regarding their individuality, training and the techniques used. The patient base was composed mainly of teenagers (33.75%) and young adults (27.45%), with referral predominantly by the patients themselves (46.79%). Among the most important facts, we can mention the lack of use of some individual protection equipment, with only 37.76% using all the features of biological safety. Final exams have been requested less frequently than initial records, and findings from the literature review is even more frightening, considering the importance of these records. Looking at the future of the profession, optimistic orthodontists did not exceed half (45%) of participants.